New insights into the diversity of strepsirrhine primates from the late early – early middle Eocene of North Africa (Algeria and Tunisia) - (:unkn) unknown (My University, 2025)
The Gour Lazib Complex in Algeria and Djebel Chambi in Tunisia are the only African regions with abundant fossil records of diverse mammals dating from the late early to early middle Eocene. Among these mammals, primates, documented by few dental remains, have long attracted much attention for their possible role in the African origin of the group to which we belong, the anthropoids. Continuing fieldwork at these localities has uncovered new dental, cranial and postcranial remains of these primates, shedding new light on their phylogenetic status. These primates, Azibiidae and Djebelemuridae, are now recognized as ‘advanced’ stem strepsirrhines, i.e., more closely related to crown Strepsirrhini (tooth-combed primates) than to any Adapiformes (other stem strepsirrhines, lacking a tooth-comb). Here, we illustrate and describe new fossil specimens (dental only) recently recovered from these two former sites. From the Gour Lazib Complex (including Glib Zegdou), in addition to the previously known azibiid taxa, Azibius trerki and Algeripithecus minutus, we describe a new, larger azibiid, Azibius magnus sp. nov., and a tiny new taxon, Lazibadapis anchomomyinopsis gen. et sp. nov., which could be a basal djebelemurid. New deciduous teeth and illustrations of earlier fossil taxa are also provided. From Chambi, in addition to Djebelemur martinezi, we identify a small azibiid, previously recognized among Djebelemur paratypes, and describe a new species, Algeripithecus minimissimus sp. nov., based on additional dental material. These new fossils extend our knowledge of the paleodiversity of these two extinct strepsirrhine families, and reveal their wider paleogeographic distribution across North Africa at the onset of the Eocene. Azibiidae were highly specialized, likely feeding on a mixed diet of exudates and fruit. This specialization allowed for remarkable diversity but ultimately led to their extinction, possibly due to ecological constraints, although th
Keywords: African Research